Technology road mapping: the issues of managing technology change. (1st January 1999) - Probert, David; Shehabuddeen, Noordin
Technology road mapping has emerged in recent years as a key management tool in formulating the link between technological resources and the exploitation of market opportunities. A powerful aid to strategy formulation and communication, the technique has the major advantage of bringing many functions within a business together around a common plan. Although there is no definitive guide to road mapping practice, the application in many different businesses has revealed a number of generic aspects. A major common factor is that technology road maps are concerned with the introduction of technology change into an organisation. This paper proposes a conceptual model of the factors significant for the successful introduction of technology change. The relevance of this framework to technology road mapping is discussed based on the in-depth experience of developing and implementing TRMs for three large companies. Also discussed briefly are results of questionnaires sent to these three companies to obtain a feedback on their post-implementation experiences.